La gestión del conocimiento como herramienta de competitividad en las organizaciones (2021)
The central objective of this project is to demonstrate the importance of knowledge management, as a new and growing factor of competitiveness and sustainability in organizations. For this, concepts, objectives, advantages used for its management will be exposed. In addition, model studies for the creation, implementation and management of knowledge will be carried out, some of them will be analyzed in order to be able to discern difficulties and determining factors that limit the achievement of the processes for the establishment and management of knowledge.